A construção das memórias íntimas de uma personagem feminina em "Fanny Hill: Memoirs of a Woman of Pleasure", de John Cleland, e na peça "The Life and Times of Fanny Hill", de April de Angelis: aproximações e distanciamentos - Fardin, Gabriela [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Este trabalho realiza uma leitura crítica da primeira obra erótica publicada em língua inglesa, Fanny Hill: Memoirs of a Woman of Pleasure (1748-49), que conta as aventuras de uma jovem prostituta, e a adaptação teatral da autora feminista April de Angelis: The Life and Times of Fanny Hill (1996), que relata os processos pelos quais Fanny Hill, uma prostituta mais velha, enfrenta ao escrever um livro encomendado. Além da análise das duas obras, este estudo apresenta uma comparação direta entre o romance e a peça, utilizando como ponto de partida para a reflexão o modo como cada uma das histórias foram contadas ao leitor, a escolha linguística dos autores, a maneira como a temática sexual foi tratada por Cleland e por Angelis e a construção das duas personagens, tão próximas e tão distantes entre si.

This paper makes a critical reading of the first erotic book published in English, Fanny Hill: Memoirs of a Woman of Pleasure (1748-49), which tells the adventures of a young prostitute, and the theatrical adaptation of feminist author April de Angelis: The Life and Times of Fanny Hill (1996), which chronicles the processes Fanny Hill, an older prostitute, faces in writing a commissioned book. In addition to the analysis of the two works, this study presents a direct comparison between the novel and the play, using as a starting point for reflection how each of the stories were told to the reader, the linguistic choice of the authors, the form sexual themes were treated by Cleland and Angelis, and the construction of the two characters, so close and so far apart.
The construction of the intimate memoirs of a female character in "Fanny Hill: Memoirs of a Woman of Pleasure", of John Cleland, and in the play "Life and Times of Fanny Hill", of April de Angelis: approaches and distances
Keywords: Fanny Hill; John Cleland; The Life and Times of Fanny Hill; April de Angelis; Literatura Inglesa; English literature